1969
DOI: 10.1111/j.1432-1033.1969.tb19628.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Properties of an Induced β‐d‐Xylosidase of Bacillus pumilus 12

Abstract: A highly specific 8-D-xylosidase with absolute glycon-substrate specificity was induced in Bacillus pumilus 12 by xylose. It was purified 34-fold by a procedure involving lysis of the cells with lysozyme, ammonium sulfate fractionation, G-75 Sephadex gel filtration and hydroxylapatite chromatography. The optimal activity was in the pH region 7.0-7.3. The isoelectric point was found to be 4.4. I n contrast to its broad complexing affinity, the hydrolytic activity was restricted to aryl @-D-xylopyranosides and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 26 publications
2
31
1
1
Order By: Relevance
“…5). In fact the average B-factor of the active site acidic et al , 1969;Chen et al, 1987) including AHA with Ki = 10" M residues in the native structure is 15.3 A2, whereas the correspondat pH 7.2. Inhibition studies of a-glucosidase, trehalase, and ing value in the complex with Tris is 16.9 A2.…”
Section: Inhibition By Trismentioning
confidence: 97%
“…5). In fact the average B-factor of the active site acidic et al , 1969;Chen et al, 1987) including AHA with Ki = 10" M residues in the native structure is 15.3 A2, whereas the correspondat pH 7.2. Inhibition studies of a-glucosidase, trehalase, and ing value in the complex with Tris is 16.9 A2.…”
Section: Inhibition By Trismentioning
confidence: 97%
“…These observations effluent was assayed for activity of /I-xylosidase, pointed out that the soluble cell-bound P-xylosidase /?-xylanase and also P-glucosidase, since it has been reported that some microbial B-glucosidases are capis of a xylobiase type. able of hydrolynng P-xylosides [19].…”
Section: Divrrsity Of 8-xylosidcise~ Outside and Inside The Cellsmentioning
confidence: 99%
“…The first bacterial /Ixylosidase isolated was from Bacillus pumilus (Kersters-Hilderson et al, 1969) and more recently the properties of a /I-xylosidase from Clostridium acetobutylicum have been reported (Lee & Forsberg, 1987). The /I-xylosidase activity of a thermophilic Thermomonospora strain has been described as notable in that it exhibits broad pH and temperature optima (Ristroph & Humphrey, 1985), although no attempt was made to isolate or purify the enzyme from crude cell extracts.…”
Section: Introductionmentioning
confidence: 99%